Black Phosphorus and Carbon Nitride Hybrid Photocatalysts for Photoredox Reactions. (4th June 2020) - Zheng, Yun; Chen, Yilin; Gao, Bifen; Lin, Bizhou; Wang, Xinchen
Abstract: The development of metal‐free photocatalysts with high efficiency, stability, and broadband solar absorption is a major challenge to realize green and sustainable chemical development. Recently, metal‐free nanohybrids (BP/CN) composed of black phosphorus (BP) and polymeric carbon nitride (CN) are emerged as photocatalytic hybrids with broadband light‐harvesting capabilities and higher photocatalytic performance. Herein, the latest progress of BP/CN hybrids for multifarious photoredox reactions is summarized. The different heterojunction types of BP/CN hybrid photocatalysts, including type I, type II, and multicomponent heterojunctions, are illustrated. Furthermore, the relevant applications of BP/CN hybrid photocatalysts for photocatalytic water splitting, CO2 photoreduction, N2 fixation, H2 O2 production, pollutant decomposition, and bacterial inactivation are discussed. An overview of the challenge in this area and the directions for the future is presented. Abstract : Metal‐free hybrid photocatalysts comprising black phosphorus (BP) and polymeric carbon nitride (CN) show promising application in solar‐to‐chemical energy conversion. This report focuses on the recent developments in heterojunction construction strategies and photocatalytic applications of BP and polymeric CN hybrid photocatalysts in various photoredox reactions, illustrating the structure−activity relationship and photocatalytic mechanism.